2013
DOI: 10.1590/s1677-5538.ibju.2013.06.06
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of hemostatic radiotherapy for bladder cancer-related hematuria in patients unfit for surgery

Abstract: Objective: The aim of our study was to assess short and mid-term clinical efficacy of external beam radiation therapy to achieve hemostasis in patients with bladder-cancer related gross hematuria who were unfit for surgery. We also assessed hypofractionation as a possible alternative option for more severe patients. Patients and Methods: Thirty-two patients were included for hemostatic radiation therapy, with two schedules based on Eastern Cooperative Oncology Group performance status. The standard treatment w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 21 publications
3
22
0
5
Order By: Relevance
“…Locarriere et al reported that 22 of 32 patients (69%) who had received 20 Gy in 5 fractions or 30 Gy in 10 fractions became hematuria-free after RT; the response rate of patients who received 20 Gy in 5 fractions was 79% [9]. For gynecological cancer, the response rate was 100% (4 of 4 patients) in our study.…”
Section: Discussionsupporting
confidence: 48%
“…Locarriere et al reported that 22 of 32 patients (69%) who had received 20 Gy in 5 fractions or 30 Gy in 10 fractions became hematuria-free after RT; the response rate of patients who received 20 Gy in 5 fractions was 79% [9]. For gynecological cancer, the response rate was 100% (4 of 4 patients) in our study.…”
Section: Discussionsupporting
confidence: 48%
“…For patients with development of symptoms, e.g. haematuria, local treatment may be feasible with radiation or embolisation . For patients who are placed on watchful waiting and develop systemic progression, metastatic UC is uniformly fatal.…”
Section: Discussionmentioning
confidence: 99%
“…Lacarriиre и соавт. провели сравнительную оценку эффективности 2 режимов фракционирова-ния: РОД 3 Гр, 10 фракций до СОД 30 Гр у 13 больных РМП и РОД 4 Гр, 5 фракций до СОД 20 Гр в течение недели у 19 пациентов [18]. Через 2 нед после начала ДЛТ купирование гематурии отмечено в 69 % случаев, при этом в 1-й группе -в 54 %, а во 2-й группе -в 79 % случаев.…”
Section: Discussionunclassified
“…Представлены результаты применения различных режимов ГФ: РОД 8,5-7,0 Гр, 2-3 фракции до СОД 17-21 Гр [8][9][10][11]; РОД 5-6 Гр, 1 или 2 фракции в неде-лю до СОД 30-36 Гр [12][13][14][15][16]; а также РОД 3,0-3,5 Гр, 10 фракций до СОД 30-35 Гр [9,17,18]. Как следует из опубликованных данных, применение подобных схем ДЛТ у больных РМП позволяет достичь палли-ативного эффекта в 40-70 % случаев.…”
Section: Introductionunclassified